2013
DOI: 10.1016/j.mayocp.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dietary Salt and Potassium Intake in Cardiovascular Health and Disease: A Review of the Evidence

Abstract: The objective of this review is to provide a synthesis of the evidence on the effect of dietary salt and potassium intake on population blood pressure, cardiovascular disease, and mortality. Dietary guidelines and recommendations are outlined, current controversies regarding the evidence are discussed, and recommendations are made based on the evidence. Designed search strategies were used to search various databases for available studies. Randomized trials of the effect of dietary salt reduction and/or increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
193
0
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(215 citation statements)
references
References 78 publications
(110 reference statements)
1
193
0
13
Order By: Relevance
“…Effect on Cardiovascular System. Several population-based studies have validated the benefits of a K-rich diet and K supplementation in the prevention and treatment of hypertension [79][80][81][82]. Though the exact mechanism is not known, several experimental studies have demonstrated the inhibitory effects of serum K on vascular smooth muscle proliferation, reducing macrophage adherence to the vascular wall, arterial thrombosis, free oxygen radicals, and reactive oxygen species [83][84][85].…”
Section: Potassium (K)mentioning
confidence: 99%
“…Effect on Cardiovascular System. Several population-based studies have validated the benefits of a K-rich diet and K supplementation in the prevention and treatment of hypertension [79][80][81][82]. Though the exact mechanism is not known, several experimental studies have demonstrated the inhibitory effects of serum K on vascular smooth muscle proliferation, reducing macrophage adherence to the vascular wall, arterial thrombosis, free oxygen radicals, and reactive oxygen species [83][84][85].…”
Section: Potassium (K)mentioning
confidence: 99%
“…Esses resultados se devem possivelmente ao aumento do consumo de alimentos industrializados em detrimento dos alimentos in natura. Além disso, o consumo excessivo ou escasso desses nutrientes pode resultar em sérias complicações para a saúde dos indivíduos [39][40][41] . Um estudo que analisou 52 publicações com o objetivo de avaliar a relação de dietas contendo alto teor de sódio e baixo teor de potássio com a pressão arterial verificou que esse padrão dietético, além de aumentar a pressão arterial, também desempenhou um papel na disfunção arterial, estrutura e função cardiovascular, aumentando a morbimortalidade da população em geral 41 .…”
Section: Discussionunclassified
“…Além disso, o consumo excessivo ou escasso desses nutrientes pode resultar em sérias complicações para a saúde dos indivíduos [39][40][41] . Um estudo que analisou 52 publicações com o objetivo de avaliar a relação de dietas contendo alto teor de sódio e baixo teor de potássio com a pressão arterial verificou que esse padrão dietético, além de aumentar a pressão arterial, também desempenhou um papel na disfunção arterial, estrutura e função cardiovascular, aumentando a morbimortalidade da população em geral 41 . Este foi o primeiro estudo realizado com carteiros pedestres da cidade de Porto Alegre com o intuito de conhecer o perfil nutricional e alimentar desses indivíduos a fim de planejar estratégias futuras para a prevenção de DCNT.…”
Section: Discussionunclassified
“…Moreover, high potassium intake may have the greatest effect when salt intake is high, and it was associated with a lower risk of death and cardiovascular events [26].…”
Section: Discussionmentioning
confidence: 99%